Health care utilization among beneficiaries with diabetes from federally qualified health centers: Analysis from a Medicaid managed care organization. Issue 1 (2nd January 2022) - Austin, Shamly; Clarke, Meredith; Zhang, Yuan; Qu, Haiyan; Pisu, Maria
Abstract: We examined health care utilization among federally qualified health center (FQHCs) users from a Medicaid managed care organization based on 2016 administrative claims data ( n  = 8, 402). FQHC users had fewer primary care visits (Adjusted Incidence Rate Ratios (aIRR): 0.82; 95% CI: 0.76–0.88) compared with non-FQHC users. Statistically significant differences were not observed in emergency department visits (aIRR: 1.19; 95% CI: 0.98–1.46) and hospitalizations (aIRR: 1.03; 95% CI: 0.80–1.34). FQHCs provide comprehensive primary care to Medicaid managed care beneficiaries with diabetes in fewer PCP visits. Results provide evidence to health policy experts and MCOs to increase provider network contracting with FQHCs.